Plastic to fuel : the effect of real plastic wastes composition - Ali Zaynal Abidin, Othman (2017)
Plastic is a major composition in municipal waste. Depleting of fossil fuel leads to exploration of alternative fuel production including converting plastic waste to fuel. The objective of this of study is to investigate the effect of real plastic waste composition on a pyrolysis process to fuels. Plastic wastes that compose of shampoo bottle, plastic bag, plastic wrapper and polystyrene were used. Thermal decomposition study of the plastic wastes was done by using Thermogravimetric Analysis. The catalyst used in this research is oil palm biomass ash catalyst. It was cleansed and calcined at 750°C (15°C.min-1) for four hours. Then, the catalyst was then crushed and sieved to have homogenized size of < 125μm. The catalyst was characterized by using Scanning Electron Microscope (SEM) with Energy Dispersive X-Ray (EDX) and Brunauer, Emmett and Teller (BET). Nitrogen gas was used to provide oxygen free condition during the investigation. The plastic waste and catalyst weight ratio was set at 10:1. The catalyst was tested in a batch one litre borosilicate reactor and heated up to 450 C for 30 minutes. The plastic wastes decomposed into liquid, solid residue and gas. The liquid product was collected in a condenser, while the uncondensed gas was collected in the gas bag. The composition of the liquid fuel was analyzed by using Mass spectrometry gas chromatography (GC-MS). The calorific value, moisture, density, turbidity, cetane and octane number of the liquid fuel were also determined. Gas composition of the gas product was determined via Thermal Conductivity Detector gas chromatography (GC-TCD). About 40% of liquid fuel was produced after the pyrolysis for shampoo bottle. The application of catalyst significantly improved the liquid production to 50% of liquid fuel. Liquid fuel quality with averagely high octane number for shampoo bottle and polystyrene are 100 and 98 respectively. Low moisture content (<3 %) was observed in all liquid fuels. The calorific value ranging from 2885.36 cal/g - 4209.31 cal/g was achieved for all plastics samples. A gas product that rich in methane (±3mol%) was obtained. In conclusion, the application of catalyst that derived from waste creates a low cost alternative fuel production via catalytic plastic waste pyrolysis.